Financial Performance and Sharia Stock Prices: Evidence from Indonesia's Halal Food and Beverage Industry - Khristina Sri Prihatin; Anggi Haerani; Yono Ali Achmad; Qobiyatul Muthoharoh (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study examined the effects of profitability, liquidity, and solvency on the Sharia stock prices of halal food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2021 period. A quantitative research approach was employed using secondary data obtained from audited annual financial statements. The sample consisted of 16 Sharia-compliant companies selected through purposive sampling, resulting in 48 firm-year observations. Multiple linear regression analysis was conducted to evaluate the effects of Return on Assets (ROA), Current Ratio (CR), and Debt-to-Equity Ratio (DER) on Sharia stock prices. The results indicated that profitability and solvency significantly affected Sharia stock prices, whereas liquidity did not have a significant effect. Simultaneously, the three financial ratios explained 40.8% of the variation in Sharia stock prices. These findings suggested that profitability and capital structure were more important than liquidity in determining stock valuation within Indonesia's Islamic capital market. However, the study was limited to the halal food and beverage manufacturing subsector and a three-year observation period. This study contributed updated empirical evidence on the financial determinants of Sharia stock prices and enriched the literature on Islamic capital markets in Indonesia.